INTEGRATED EFFECT OF NITROGEN AND POTASSIUM WITH OR WITHOUT SULPHUR AND FARM YARD MANURE ON POTATO TUBER YIELD, STORAGE QUALITY AND SOIL FERTILITY STATUS - Mondal, S S; Saha, Mithun; Acharya, D; Patra, D; Chatterjee, S. (Potato Journal, 2013)
An experiment was conducted during 2000-01 and 2001-02 at Farmer’s field, Chandamari, Nadia to evaluate the integrated effect of N and K with or without S and FYM on production and soil fertility status in potato under new alluvial soil. Different sources, time of application and doses of potassium and sulphur nutrition and farm yard manure were considered. Maximum dry matter accumulation and tuber yield was recorded under 120, 100 and 100 kg/ha of N, P and K, respectively along with FYM application. Sulphur nutrition and split application of K also resulted in positive influence on potato production. FYM application along with chemical fertilizer showed highest net production value, lowest percent disease index and minimum wight loss at 45 days after storage. Build up of soil fertility status especially N, P and K was recorded with chemical fertilizer + FYM.